Assessment of Alveolar Ridge Defects based on Sibert’s Classification - A Retrospective Study - Anubhav Das1 , Revathi Duraisamy2 , Ravindra Kumar Jain3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Alveolar ridge defect may occur due to injury,trauma,normal healing after extraction, denture wear andperiodontitis. Based on sibert’s classification, it can be classified into three classes: class I (buccolingual lossof tissue), class II (apico coronal loss of tissue) and class III (both loss of tissue). It is important to close theridge defect by replacing the tooth loss and to achieve good esthetic, phonetic and mastication. The aim ofthis study was to assess the prevalence of alveolar ridge defects using seibert’s classification among partiallyedentulous patients.This study was conducted in a university setting among the outpatient population of adental college.We reviewed patients records and analysed the data of 86000 patients between June 2019 andMarch 2020. 32,837 patients data were included from 86000 patients and were assessed and the data wastabulated in excel and later was imported to SPSS software by IBM and descriptive statistics were doneand results were analysed graphically. The statistical analysis were performed using chi-square test.Basedon the results, 50.5% males,51.4% females and 40% transgender have class I alveolar ridge defects; 0.7%male,0.8% females and 0% transgender have class II alveolar ridge defects;1.3 % males,1.4% females and0% transgenders have class III alveolar ridge defects; 47.5% males, 46.4% females and 60% transgenderhave normal edentulous ridge.To conclude, the Sibert’s classification helps in suggesting a proper treatmentplan for the patient to ensure that the treatment outcomes turn out to be successful.